Identifying risk factors for traumatic injury (TBI) due to road traffic accidents (RTA) and strategies to reduce the burden of secondary brain injury - Alberts, Kriste (Department of Public Health and Family Medicine, 2025)
Background: There is a major knowledge gap in South Africa about detailed risk factors contributing to TBI due to RTAs in children. The objectives of this study were to map the burden of disease and examine circumstantial and clinical information to inform potential intervention strategies. Methods: This was a descriptive study of patients with TBI admitted to the Red Cross War Memorial Children's Hospital in Cape Town, Western Cape. A retrospective analysis of basic demographic and clinical data were performed from a large database of children admitted with severe TBI. More detailed information about the circumstances of RTAs causing TBI were prospectively collected through interviews with caregivers. Findings: From a database of 511 paediatric patients with severe TBI (age 13 or less), 403 (78.9%) sustained injuries in RTAs, mostly as pedestrians (71.7%). Males were more often injured (66%) and the median age was 6.8 years. The median time from the accident to tertiary hospital admission was three hours, to obtaining a CT scan was 4.5 hours, and to ICU admission was nine hours. With respect to the circumstances of RTAs, 155 interviews were conducted of which 80.7% involved pedestrian incidents. In 34 incidents (22%), more than one person was injured. Among these, 19 involved parents, with 17 of them (89.5%) dying from their injuries. Among pedestrians, 62% were injured while crossing the road and 57.5% were unaccompanied by an adult. Most commonly, the injured first attended the nearest clinic or day hospital (46%) by travelling with a personal vehicle (53%). Local areas that experienced the most RTAs were Gugulethu (7.7%), Khayelitsha (5.3%) and Mitchells Plain (5.3%). Interpretation: The study indicates a high incidence of RTAs as a cause of TBI in South African children, particularly among pedestrians. The high rate of unaccompanied children crossing roads, suggests a need for improved road safety education and adult supervision. The clustering of RTAs in specific local communities' points to the need for targeted interventions in highrisk locations. The high mortality rate among parents involved in RTAs with their children underscores the broader impact of these accidents on families and communities. Funding: This work was supported by the University of Cape Town Postgraduate Funding Office and the Paediatric Neurosurgery Unit.